The Influence of Promotions and Interest Rates on ASN Customer Decisions in Taking Consumer Credit PT Bank Sulselbar Cabang Parepare - Ilahi, Andi Alfianto Anugrah; Arifuddin; Alimuddin, Firman (International Journal of Management and Business Intelligence, 2024)
This research aims to find out whether promotions and interest rates have a partial and simultaneous effect on ASN customers' decisions in taking consumer credit at PT. Bank Sulselbar Parepare Branch. Multiple linear regression is the analytical technique employed, along with partial and simultaneous tests for validity, reliability, and hypothesis testing. The study's findings indicate that promotion (X1) has a somewhat substantial impact on ASN customers' decisions in taking consumer credit at PT. Bank Sulselbar Parepare Branch, this is shown based on the calculated promotional t value of 4.431 > t table 1.967 with a significance value of 0.000 < 0.05, the interest rate (X2) has a positive and partially significant effect on ASN customers' decisions in taking consumer credit at PT. Bank Sulselbar Parepare Branch, this is shown by the calculated t value of 13.627 > t table 1.967 with a significance value of 0.000 < 0.05. All Pearson correlation or calculated r values ​​from statements related to promotions and interest rates have an r table value greater than 0.107, so all instruments are declared valid. Simultaneously promotions and interest rates influence ASN customers' decisions in taking consumer credit at PT. Bank Sulselbar Parepare Branch, this is shown based on the calculated F value of 5,035.590 > F table 3.023, with a significance level of 0.000 < 0.05.